Self-Medication Towards Antibiotic Use Among Non- Medical University Staff (Conference Paper )# - Al-Tukmagi, Haydar; Al-Qazaz, Harith; Shanshal, Sadeel; Al-Kaisey, Muhanad (Iraqi Journal of Pharmaceutical Sciences, 2023)
The use of antibiotics without prescription (self-medication) is growing globally and is associated with increased bacterial resistance, ineffective treatment and adverse reactions. This study aimed at assessing the practice of antibiotic self-medication in the Iraqi population. A cross-sectional study design was adopted in this work. The sample was comprised of 303 staff members from the non-medical colleges in Iraq. An online questionnaire was distributed between the 29th of June to the 14th of September 2021 to collect data including socio-demographic characteristics and questions about antibiotic self-medication. Most of the participants had a university degree and a moderate monthly income. The majority (88%) have practiced self-medication at least once before. A “simple” condition and convenience were the main motivators behind self-medication, which was mainly used for sore throat, fever and cough. Own experience was the most reported determining factor for selecting an antibiotic, and community pharmacies were the main source for obtaining the antibiotics. About 40% of the participants admitted to switching the antibiotic or changing its dose during the treatment course. Self-medication with antibiotics is a major issue in our community and measures have to be taken to reduce its impact on public health through the development of bacterial resistance.